Neutrophil to lymphocyte ratio in patients with vitiligo - Berna Solak (Advances in Dermatology and Allergology, 2017)
Introduction : There are a few studies showing an increased risk of insulin resistance, metabolic syndrome, and oxidative stress in patients with vitiligo. Aim : To investigate whether systemic inflammation is increased in vitiligo patients in a case-control study design. Material and methods : Nonsegmental vitiligo patients who had been followed at the outpatient dermatology clinic of a university-affiliated teaching hospital, and healthy controls were enrolled in the study. Patients who were receiving systemic treatments and having a systemic disease such as diabetes mellitus and thyroiditis were excluded. Demographic features were recorded and peripheral blood samples were taken from all participants to study serum whole blood count, creatinine, and C-reactive protein (CRP). Results : Fifty patients with localized vitiligo, 43 patients with generalized vitiligo, and 50 healthy volunteers were enrolled in the study. Neutrophil to lymphocyte ratio and serum CRP levels were significantly higher in patients who have generalized vitiligo than those with localized vitiligo and healthy controls. However, there was no significant difference regarding neutrophil to lymphocyte ratio (NLR) and CRP between localized vitiligo and control groups. Conclusions : Patients with generalized vitiligo seem to have increased systemic inflammation compared with localized vitiligo and control subjects in our cohort. To the best of our knowledge, this is the first study in the literature showing increased NLR values in generalized vitiligo patients. Further studies with cardiovascular disease markers are required to elicit this association better.